Physicochemical and pharmacokinetic evaluation of praziquantel co-crystals by varying the spacer group of co-crystal formers - Muhammad Wasim; Abdul Mannan; Azim, Tabinda; Ali Khan, Rashid; Alotaibi, Ghallab; Muhammad Amer; Muhammad Shafique; Muhammad Asghar Khan; Gul, Sumaira; Hussain, Izhar (Penerbit Universiti Kebangsaan Malaysia, 2022)
The research work focuses on investigating the effects of spacer group (varying aliphatic chain length=n) of co-crystal formers (oxalic acid (OA, n=0), (malonic acid (MA, n=1), (succinic acid (SA, n=2), (glutaric acid (GA, n=3), and (adipic acid (AA, n=4) on the physicochemical properties and oral bioavailability of praziquantel (PZQ) co-crystals. For this purpose, different co-crystals of PZQ with dicarboxylic acid co-crystal formers (OA, MA, SA, GA, and AA) were synthesized. These co-crystals were characterized by powder X-ray diffractometry (XRPD), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), and thermogravimetry (TG) techniques. The in-vitro (solubility and dissolution) and in-vivo pharmacokinetic (P.K) studies were performed for PZQ co-crystals. Additionally, the effect of polymer hydroxypropyl cellulose (HPC) on the formation of PZQ co-crystals was also investigated. According to the study results, PZQ-SA co-crystal showed improved solubility, dissolution, and oral bioavailability. Overall, the solubility, dissolution, and oral bioavailability are consistent with each other. The order of improved solubility, dissolution, and oral bioavailability is observed as consistent like PZQ-SA > PZQ-AA > PZQ-GA > PZQ-OA > PZQ-MA > pure PZQ. Concerning HPC polymer effects, PZQ-OA, PZQ-MA, PZQ-GA, and PZQ-AA co-crystals were formed successfully in the presence of HPC polymer but the PZQ-SA co-crystal was inhibited.